2005
DOI: 10.1038/modpathol.3800283
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of tuberin and some potential tumorigenic factors in 60 patients with uterine leiomyomata

Abstract: Human uterine leiomyomata are the most common tumors in women of reproductive age. The pathogenesis of leiomyomata remains unknown. An animal model of Eker rats with deleted tuberous sclerosis complex gene 2 (tuberin) shows increased incidence of leiomyomata. The role of tuberin in human leiomyomata is unknown. In this study, we designed a tissue microarray with tissue cores of leiomyomata and the matched myometrium from 60 hysterectomy specimens. We examined the expression of tuberin and tuberous sclerosis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…Previous studies in our laboratory (5,8) and by others (7,(9)(10)(11) have indicated that the IGF-I pathway plays an important role in uterine leiomyoma development and growth. IGF-I is a single-chain polypeptide whose structure is highly similar to that of proinsulin.…”
Section: Differential Expression Of Receptor Tyrosine Kinases (Rtks) mentioning
confidence: 99%
“…Previous studies in our laboratory (5,8) and by others (7,(9)(10)(11) have indicated that the IGF-I pathway plays an important role in uterine leiomyoma development and growth. IGF-I is a single-chain polypeptide whose structure is highly similar to that of proinsulin.…”
Section: Differential Expression Of Receptor Tyrosine Kinases (Rtks) mentioning
confidence: 99%
“…Corepressor NCoR1 and coactivator SRC1, which are extensively expressed in the uterus [56, 58], modulate the action of SPRM-bound PRs [59]. …”
Section: Discussionmentioning
confidence: 99%
“…Three transcriptional targets of GR (Mittelstadt and Ashwell, 2003;Phuc Le et al, 2005) appeared downregulated in FH deficiency and in leiomyomas (ABCA1, FNTA and LMO4), and GR expression was downregulated. GR is a known repressor of stem cell number and proliferation (Chebotaev et al, 2007), and has been reported to be downregulated in leiomyomas (Wei et al, 2005). Downregulation of GR signaling may thus contribute to lower differentiation phenotype in FH smooth muscle cells and to the formation of the leiomyomas.…”
Section: Srf-fos-junb Pathway In Myomasmentioning
confidence: 99%